2015
DOI: 10.1007/s40979-015-0006-2
|View full text |Cite
|
Sign up to set email alerts
|

Disciplinary action for academic dishonesty: does the student’s gender matter?

Abstract: The purpose of this study is to identify if gender differences exist with respect to conviction of university students for academic dishonesty. To investigate this phenomenon, data from the Swedish National Agency for Higher Education (SNAHE) and from disciplinary boards of several Swedish universities were evaluated from a gender perspective. To identify whether the penalty severity for academic dishonesty is gender biased, the ratio of suspensions/warnings for male and female students was calculated. It was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 26 publications
2
13
1
1
Order By: Relevance
“…The behaviors listed from lesser to greater offenses are as follows: cheat sheets, unauthorized collaboration, plagiarism, forging documents, disruptive behavior, and sexual/ethnic harassment. The most frequently reported form of academic misconduct was plagiarism and fabrication, and the least was sexual/ethnic harassment (Witmer & Johansson, ).…”
Section: Academic Dishonesty and Gender: The Case Of Swedensupporting
confidence: 70%
See 3 more Smart Citations
“…The behaviors listed from lesser to greater offenses are as follows: cheat sheets, unauthorized collaboration, plagiarism, forging documents, disruptive behavior, and sexual/ethnic harassment. The most frequently reported form of academic misconduct was plagiarism and fabrication, and the least was sexual/ethnic harassment (Witmer & Johansson, ).…”
Section: Academic Dishonesty and Gender: The Case Of Swedensupporting
confidence: 70%
“…Based on these statistics and self‐reports on academic dishonesty behavior, it was found that female students were less represented in disciplinary matters. Furthermore, there was no systematic gender bias in the severity of penalties whether it be warnings or suspensions (Witmer & Johansson, ).…”
Section: Academic Dishonesty and Gender: The Case Of Swedenmentioning
confidence: 99%
See 2 more Smart Citations
“…Plagiarism and other practices of academic misconduct constitute a growing problem as these actions spoil the coherence of educational process and probably debilitate the reliability of educational programs (Witmer & Johansson, 2015). At this point, a significant number of studies have provided considerable advice on the ways dealing with plagiarism regarding educative, preventative and punitive precautions (Beasley, 2004;Bretag & Mahmud, 2009;Carroll & Appleton, 2001;Coughlin, 2015;Park, 2003;Sayed & Lento, 2015).…”
Section: Introductionmentioning
confidence: 99%